Oxidative degradation of biorefinery lignin obtained after pretreatment of forest residues of Douglas Fir. (December 2016) - Srinivas, Keerthi; de Carvalho Oliveira, Fernanda; Teller, Philip Johan; Gonҫalves, Adilson Roberto; Helms, Gregory L.; Ahring, Birgitte Kaer
Graphical abstract: Biorefinery lignin stream obtained after wet explosion pretreatment of forest residues were further degraded using wet oxidation to produce high-value biochemicals. The biorefinery lignin stream was characterized to understand efficiency of oxidative degradation process. Highlights: Biorefinery lignin was obtained from wet explosion pretreatment of forestry residues. The biorefinery lignin was characterized using NMR and FTIR. Alkaline wet oxidation of biorefinery lignin produced organic acids as primary products. Best wet oxidations conditions were found to be 11.7 wt% alkali loading and 15 min. Higher severity oxidation treatment increased vanillin production. Abstract: Harvested forest residues are usually considered a fire hazards and used as "hog-fuel" which results in air pollution. In this study, the biorefinery lignin stream obtained after wet explosion pretreatment and enzymatic hydrolysis of forestry residues of Douglas Fir (FS-10) was characterized and further wet oxidized under alkaline conditions. The studies indicated that at 10% solids, 11.7 wt% alkali and 15 min residence time, maximum yields were obtained for glucose (12.9 wt%), vanillin (0.4 wt%) at 230 °C; formic acid (11.6 wt%) at 250 °C; acetic acid (10.7 wt%), hydroxybenzaldehyde (0.2 wt%), syringaldehyde (0.13 wt%) at 280 °C; and lactic acid (12.4 wt%) at 300 °C. FTIR analysis of the solid residue after wet oxidation showed that the aromatic skeletal vibrations relating to lignin compounds increased with temperature indicating that higher severity could result in increased lignin oxidation products. The results obtained, as part of the study, is significant for understanding and optimizing processes for producing high-value bioproducts from forestry residues.